QRICH1 mutations cause a chondrodysplasia with developmental delay. Issue 1 (26th October 2018) - Lui, Julian C.; Jee, Youn Hee; Lee, Audrey; Yue, Shanna; Wagner, Jacob; Donnelly, Deirdre E.; Vogt, Karen S.; Baron, Jeffrey
Abstract : In many children with short stature, the etiology of the decreased linear growth remains unknown. We sought to identify the underlying genetic etiology in a patient with short stature, irregular growth plates of the proximal phalanges, developmental delay, and mildly dysmorphic facial features. Exome sequencing identified a de novo, heterozygous, nonsense mutation (c.1606C>T:p.R536X) in QRICH1 . In vitro studies confirmed that the mutation impaired expression of the QRICH1 protein. SiRNA‐mediated knockdown of Qrich1 in primary mouse epiphyseal chondrocytes caused downregulation of gene expression associated with hypertrophic differentiation. We then identified an unrelated individual with another heterozygous de novo nonsense mutation in QRICH1 who had a similar phenotype. A recently published study identified QRICH1 mutations in three patients with developmental delay, one of whom had short stature. Our findings indicate that QRICH1 mutations cause not only developmental delay but also a chondrodysplasia characterized by diminished linear growth and abnormal growth plate morphology due to impaired growth plate chondrocyte hypertrophic differentiation. Abstract :